Aplicación web para la gestión de ventas e inventario de la empresa la fábrica del jean en la ciudad de Pelileo - Panta Pallaroso, Carlos Eduardo (2025)
This work is divided into several chapters, tending to the organized and sequential development of the same in order to improve the management of sales and inventory of the company “La Fabrica del Jean”. The contribution of each of the chapters is described below. In the first part, the background, approach and formulation, delimitation of the problem where an overview of the sales and inventory management of the company “La Fabrica del Jean” has been specified. There is an introduction regarding the fundamental research problem of the project to be carried out, and other aspects are also established, such as: objectives and justification of the problem. In the first chapter, the theoretical framework is developed, which covers all the elements that make up the web application to be carried out in order to improve the management of sales and inventory control of the company “La Fabrica del Jean”. The second chapter establishes the methodology and analysis techniques in order to obtain a qualified proposal through surveys and interviews. The third chapter develops the outline of the proposal, which consists of the evaluation and design of the present topic of the integrative project, with the help of the previous research carried out. In addition, general conclusions, recommendations, bibliography and annexes are included.